(untitled) (Ushuluddin International Conference (USICON), 2017)
The pilgrimage space provides multiple discourse that can be traced, not exceptionally the feminism view. The difference perspective to see it as the sacred place that should be maintained, articulated how woman position should be woman religiosity in pilgrims. Here, the writer tries to examine that woman religiosity is the